2018
DOI: 10.1523/jneurosci.1165-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Hexakisphosphate Kinase-2 in Cerebellar Granule Cells Regulates Purkinje Cells and Motor Coordination via Protein 4.1N

Abstract: Inositol hexakisphosphate kinases (IP6Ks) regulate various biological processes. Among pyrophosphates generated by IP6Ks, diphosphoinositol pentakisphosphate (IP7), and bis-diphosphoinositol tetrakisphosphate have been extensively characterized. IP7 is produced in mammals by a family of inositol hexakisphosphate kinases, IP6K1, IP6K2, and IP6K3, which have distinct biological functions. We report that IP6K2 binds protein 4.1.N with high affinity and specificity. Nuclear translocation of 4.1N, which is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
(23 reference statements)
0
20
0
Order By: Relevance
“…Both IP6K2 and 4.1N are highly enriched in cerebellar granule cells. Their interaction controls the morphology of Purkinje cells and cerebellar synapses [57]. Therefore, the contribution of 5-IP7 to the cerebellar control by IP6K2 warrants further investigation.…”
Section: Neurological Effectsmentioning
confidence: 98%
See 2 more Smart Citations
“…Both IP6K2 and 4.1N are highly enriched in cerebellar granule cells. Their interaction controls the morphology of Purkinje cells and cerebellar synapses [57]. Therefore, the contribution of 5-IP7 to the cerebellar control by IP6K2 warrants further investigation.…”
Section: Neurological Effectsmentioning
confidence: 98%
“…IP6K1 KO mice exhibit impaired locomotion without unaffected motor coordination under basal conditions [55]; however, the locomotion of IP6K2 KO mice is impaired locomotive, including a reduced latency to fall off the rotarod, notable decrease in stride length, and speed of movement [57]. This indicates defective motor coordination.…”
Section: Neurological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many molecules, including α7 acetylcholine receptor (α7AChr) ( Kanno et al, 2013 ), inositol 1,4,5-trisphosphate receptor type 1 (IP3R1) ( Zhang et al, 2003 ; Fukatsu et al, 2004 ; Fukatsu et al, 2006 ; Fiedler and Nathanson, 2011 ), GluR1/4 13,14 , GluK1/2/3 15,16 , metabotropic glutamate receptor 8 (mGluR8) ( Rose et al, 2008 ), K-Cl co-transporter 2 (KCC2) ( Li et al, 2007 ; Horn et al, 2010 ), D2 and D3 dopamine receptors (D2/3Rs) ( Binda et al, 2002 ; Kabbani and Levenson, 2006 ), Ca2 + -calmodulin serine kinase (CASK) ( Cohen et al, 1998 ; Biederer and Sudhof, 2001 ; Mburu et al, 2006 ), nuclear mitotic apparatus (NuMA) ( Ye et al, 1999 ; Ilies et al, 2012 ), phosphoinositide 3 kinase enhancer (PIKE) ( Ye et al, 2000 ), inositol hexakisphosphate kinase 2 (IP6K2) ( Nagpal et al, 2018 ), cell adhesion molecule (CAM) 1/3 29,30 , βII spectrin ( Wang et al, 2018 ), flotillin-1 32 , pp1 ( Wang et al, 2016 ), and 14-3-3 34-36 , have been identified as 4.1N binding partners. Although 4.1N performs different functions depending on specific tissue localization, 4.1N predominantly functions as a scaffolding protein in signaling transduction by locating, supporting, and coordinating multiple partners.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, elevated concentrations of myo-inositol were detected in the anterior cingulated of bipolar adolescents when compared to healthy individuals [4]. Remarkably, highly increased levels of myoinositol were found in cerebral white matter in a new Vsyndrome characterized by hypomyelination with atrophy of the basal ganglia and the cerebellum [5], while others have recently shown that a phosphorylator of inositol, inositol hexakisphosphate kinase-2 in cerebellar granule cells, regulates Purkinje cell morphology and cerebellar synapses [6]. Determining myo-inositol concentration during human brain development provides essential clues concerning its functions in the cerebellum [7,8] and allows subsequent, non-invasive therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%